Ludicity in Teaching Pronunciation of Polish as a Foreign/Second Language (Ludicity in (Glotto)Didactic, 2020)
The aim of this paper is to check whether elements of the ludic strategy are used in teaching pronunciation of Polish as a foreign/second language. The results were based on an analysis of phonodidactic materials, including the offer of the publishing market connected with gamification. As a summary, it shows examples of popular games, which can be successfully adapted to practise correct perception and pronunciation.